2011
DOI: 10.1590/s1415-47572011005000054
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and phylogenetic analysis of the ERF gene family in cucumbers

Abstract: Members of the ERF transcription-factor family participate in a number of biological processes, viz., responses to hormones, adaptation to biotic and abiotic stress, metabolism regulation, beneficial symbiotic interactions, cell differentiation and developmental processes. So far, no tissue-expression profile of any cucumber ERF protein has been reported in detail. Recent completion of the cucumber full-genome sequence has come to facilitate, not only genome-wide analysis of ERF family members in cucumbers the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
87
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 60 publications
6
87
1
Order By: Relevance
“…On the other hand, the highly conserved motif number and position among members in each HD-ZIP subfamily in peach also implies that they may have similar functions or a complex pattern of overlapping functions. As previously concluded, proteins within a subfamily that share motifs are likely to share similar functions (Hu and Liu, 2011). In Arabidopsis, the 5 members of HD-ZIP III show a close relationship in vascular development (Baima et al, 2001;McConnell et al, 2001;Ohashi-Ito et al, 2002;Zhong and Ye, 2004;Prigge et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…On the other hand, the highly conserved motif number and position among members in each HD-ZIP subfamily in peach also implies that they may have similar functions or a complex pattern of overlapping functions. As previously concluded, proteins within a subfamily that share motifs are likely to share similar functions (Hu and Liu, 2011). In Arabidopsis, the 5 members of HD-ZIP III show a close relationship in vascular development (Baima et al, 2001;McConnell et al, 2001;Ohashi-Ito et al, 2002;Zhong and Ye, 2004;Prigge et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…It is widely accepted that the intron/exon position pattern provides clues to evolutionary relationships (Hu and Liu, 2011). Hu et al (2012) reported that 4 (18%) of 22 Populus HD-ZIP I members had no introns in their coding regions, and this phenomenon did not exist in other Populus HD-ZIP subfamilies.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of the complete genome sequences and the previous identification of ERF/AP2 superfamily genes from some plant species (Nakano et al, 2006;Licausi et al, 2010;Hu and Liu, 2011) enabled the comparison of individual families and groups, basing the classification of these genes on Arabidopsis (Nakano et al, 2006) as a criterion. Overall (Table 1), the AP2/ERF superfamily has a similar number of genes in peach and cucumber, which is less than that in Arabidopsis (147), grapevine (149), and rice (180).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely accepted that the intron/exon position pattern provides clues about evolutionary relationships (Hu and Liu, 2011). Sakuma et al (2002) reported that most genes in the ERF family of Arabidopsis possess no introns, with only 4 genes having an intron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation